2014
DOI: 10.1007/s10750-014-2075-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of glucose and peat extract additions on the spring recruitment of Gonyostomum semen from the sediments

Abstract: The effect of two various forms of DOC on the Gonyostomum semen recruitment from sediments was conducted under experimental laboratory conditions. We tested the hypothesis that DOC is a factor enhancing spring recruitment of the species by exposing sediments from a humic lake with a 17-year bloom history, to three various DOC additions (two solutions of glucose and one solution of a peat extract). Sediments and lake water were incubated for 14 days at 16°C, in 14:10 h light:dark cycle, with germling and adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…2008, Peczula et al. 2015, Hagman et al. 2019), and iron, being able to grow at low light intensities might be G. semen ’s main competitive advantage in brown water lakes.…”
Section: Discussionmentioning
confidence: 99%
“…2008, Peczula et al. 2015, Hagman et al. 2019), and iron, being able to grow at low light intensities might be G. semen ’s main competitive advantage in brown water lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Other common components of phytoplankton were: Peridinium inconspicuum (Dinophyceae), Dinobryon divergens (Chrysophyceae) and Gonyostomum semen (Raphidophyceae) (Grabowska and Górniak, 2004). The last species is a large flagellate (length 36-92 mm, width 23-69 mm) that forms blooms in dystrophic lakes of Poland (Hutorowicz et al, 2006;Pęczuła et al, 2015). Many other studies have shown an increase in the geographical distribution and bloom incidence of G. semen in Northern Europe during recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…In autumn, sexual reproduction in G. semen occurs through fusion of haploid gametes to a motile planozygote ( Figueroa and Rengefors, 2006 ; Lebret et al , 2012 ; Rengefors et al , 2012 ), which encysts in the water column and sinks to the sediment. The cysts germinate after a dormancy period of at least 11 weeks ( Rengefors et al , 2012 ), but recruitment rates from phytoplankton cysts may vary depending on environmental variables, such as phosphorus and DOC concentrations ( Rengefors et al , 1998 ; Findlay et al , 2005 ; Pęczuła et al , 2014 ). Highest germination rates in G. semen were reported in late spring after 24 weeks of dormancy ( Rengefors et al , 2012 ).…”
mentioning
confidence: 99%